2023
DOI: 10.1021/acsomega.3c00645
|View full text |Cite
|
Sign up to set email alerts
|

Homobimetallic Au(I)–Au(I) and Heterotrimetallic Au(I)–Fe(II)–Au(I) Complexes with Dialkyldithiophosphates and Phosphine Ligands: Structural Characterization, DFT Analysis, and Tyrosinase Inhibitory and Biological Effects

Abstract: The role of bridging and terminal ligand electronic and steric properties on the structure and antiproliferative activity of two-coordinated gold(I) complexes was investigated on seven novel binuclear and trinuclear gold(I) complexes synthesized by the reaction of either Au2(dppm)Cl2, Au2(dppe)Cl2, or Au2(dppf)Cl2 with potassium diisopropyldithiophosphate, K[(S-O i Pr)2], potassium dicyclohexyldithiophosphate, K[(S-OCy)2], or sodium bis(methimazolyl)borate, Na(S-Mt)2, which afforded air-stable gold(I) complexe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 103 publications
0
4
0
Order By: Relevance
“…Therefore, in our research work, we set out to explore the derivative reactions of the simplest NHC-M-Cl system to find out more about the structural features of the resulting heteroleptic metal complexes. Also, as part of an ongoing chemistry in our group exploring the bioinorganic chemistry of sulfur donor ligands, we functionalized NHC-M­(I)-Cl (M = Ag and Au) complexes with dialkylditihiophosphate and bis­(2-mercapto-1-methylimidazolyl)­borate ligands. Sodium or potassium salts of these two ligand classes are benchtop-stable and form thermally stable metal complexes for different applications. To our best knowledge, this is the first report about the coordination of these sulfur donor ligands to the silver­(I) gold­(I) metal ions having NHC ligands. As mentioned above, the stability of NHC complexes of silver­(I) and gold­(I) in physiological conditions is vital in their application as metallodrugs.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…Therefore, in our research work, we set out to explore the derivative reactions of the simplest NHC-M-Cl system to find out more about the structural features of the resulting heteroleptic metal complexes. Also, as part of an ongoing chemistry in our group exploring the bioinorganic chemistry of sulfur donor ligands, we functionalized NHC-M­(I)-Cl (M = Ag and Au) complexes with dialkylditihiophosphate and bis­(2-mercapto-1-methylimidazolyl)­borate ligands. Sodium or potassium salts of these two ligand classes are benchtop-stable and form thermally stable metal complexes for different applications. To our best knowledge, this is the first report about the coordination of these sulfur donor ligands to the silver­(I) gold­(I) metal ions having NHC ligands. As mentioned above, the stability of NHC complexes of silver­(I) and gold­(I) in physiological conditions is vital in their application as metallodrugs.…”
Section: Introductionmentioning
confidence: 89%
“…According to the results, while the highest and lowest inhibitory potencies were observed for the complex 3 (inhibition rate 80%) and complexes 1 and 7 (with an inhibition rate ∼27% for both complexes), respectively, other complexes showed moderate inhibitory effect against diphenolase activity of the enzyme (Table ). Complex 3 exhibited outstanding potential, which is evident from its lower IC 50 (10 μM) value compared to the standard inhibitor, kojic acid (IC 50 16 μM). ,,, Considering that all the tested complexes have the five-membered imidazol-2-ylidene, it seems that this moiety does not play an effective role in the enzyme inhibition, and since complex 3 has close structural similarities with other complexes (particularly with complexes 1 and 2 ). It can be suggested that the metal center and the substituent type are the most determinant factors for the inhibitory potency of these series compounds.…”
Section: Computational Studiesmentioning
confidence: 99%
See 2 more Smart Citations